1987
DOI: 10.1136/thx.42.2.126
|View full text |Cite
|
Sign up to set email alerts
|

Impaired tracheobronchial clearance in bronchiectasis.

Abstract: Tracheobronchial clearance was measured by a radioaerosol technique in 12 patients with bronchiectasis, seven patients with chronic obstructive lung disease expectorating mucoid sputum daily (group X), eight patients with chronic obstructive lung disease but negligible sputum expectoration (group Y), and 10 healthy subjects. The patients with bronchiectasis all expectorated purulent sputum daily (mean wet weight 47 g/day), had reduced forced expiratory volume in one second (FEV1) (mean 47 5% predicted), and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(29 citation statements)
references
References 12 publications
(1 reference statement)
3
26
0
Order By: Relevance
“…The majority of subjects had extensive bronchiectasis and poor baseline clearance (,10% over 60 min), consistent with previous findings [1][2][3][4][5]. However, the majority of subjects had improved clearance, which was dose dependent after mannitol.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The majority of subjects had extensive bronchiectasis and poor baseline clearance (,10% over 60 min), consistent with previous findings [1][2][3][4][5]. However, the majority of subjects had improved clearance, which was dose dependent after mannitol.…”
Section: Discussionsupporting
confidence: 81%
“…ronchiectasis patients usually have increased and persistent mucus secretion along with impaired mucociliary transport, which results in mucus accumulation, cough and recurrent infections [1][2][3][4][5]. Most patients with bronchiectasis are troubled by the disease and have a poor quality of life [6,7].…”
mentioning
confidence: 99%
“…The nasal mucociliary clearance in controls of this study was 7.84 ± 0.92) minutes, which was significantly longer in patients with bronchiectasis. Similar result was reported by Currie et al, 19 who measured tracheobronchial clearance by a radiosol technique in 12 patients with bronchiectasis and found that clearance in the first 6 hours after inhalation of radioaerosol was significantly slower in patients with bronchiectasis. …”
supporting
confidence: 77%
“…Whereas in chronic bronchitis [39], bronchiectasis [40] and cystic fibrosis [41], mucociliary clearance is delayed, giving bacteria that have adhered to mucus time to produce virulence factors (table 1) in sufficient quantities to establish the infection. Bacterial infection attracts leucocytes into the airways, many of which eventually degenerate releasing deoxyribonucleic acid (DNA) into the secretions making them more viscous and difficult to clear [42,43].…”
Section: Bacterial Interactions With Mucusmentioning
confidence: 99%